The ovarian follicular reserve after electrosurgical treatment of ovarian endometriomas - N V Matveeva (Гинекология, 2013)
Analysisofthe results of surgical treatment in 76 patients of reproductive age after endosurgicalcuration of ovarian endometriomas has revealed that monopolar coagulation diminished an ovarian follicular reserve,modern markers of which (inhibin B and Müllerian inhibiting substance) were used.The assessment of frequency of approach of pregnancy within 12 months after expeditious treatment.